Trophic Diversity and Food Web Structure of Vegetated Habitats Along a Coastal Topographic Gradient - Li, Xiaoxiao; Yang, Wei; Sun, Tao; Yang, Zhifeng (Frontiers in Marine Science, 2022)
Land–sea interactions in coastal wetlands create heterogeneous vegetated habitats with regular zonation along a topographic gradient. However, it’s unclear how the trophic diversity of communities and trophic structure of food webs change along the gradient. Here, we investigated the empirically resolved food web structure and trophic diversity across four vegetated habitats (Phragmites australis, Suaeda salsa, Spartina alterniflora, and Zostera japonica seagrass) along a gradient from upland to near-shore waters in the Yellow River Delta wetland. We quantified δ13C and δ15N of carbon sources (detritus, primary producers) and consumers (zooplankton, macroinvertebrates, fish). δ13C and δ15N of the carbon sources and consumers differed significantly among the four habitats. Carbon sources and consumers became more 13C-enriched and 15N-enriched along the gradient, respectively. The consumer trophic position was higher in the S. salsa habitat than in the seagrass habitat, followed by the S. alterniflora and P. australis habitats. The habitat formed by invasive S. alterniflora had the lowest corrected standard ellipse areas in the δ13C vs. δ15N plots for the basal carbon sources and all consumers combined, and the lowest Layman community metrics for the δ13C range, total area, and centroid distance; thus, trophic groups in this habitat had the lowest isotopic trophic diversity. Using a Bayesian isotope mixing model, we found that consumer diet compositions differed greatly among the habitats where the consumer was present, except for shrimps and polychaetes. Food web topological properties (species richness, number of trophic links, linkage density, proportions of intermediate consumers and omnivores) increased along the gradient. Generally, habitat heterogeneity created highly variable food webs. Our results provide insights into the spatial variation in coastal ecosystems along a topographic gradient, and demonstrate the need to protect habitat heterogeneity in coastal wetlands, combined with adaptive management to control invasive species.